1997
DOI: 10.1002/hep.510260419
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis of vesicular pH in rat hepatocytes after ethanol administration

Abstract: We examined the effect of ethanol administration on in-sponsible in part for a net hepatic protein gain in ethanolfed animals. 1,2 More recently, we showed that decreased degtravesicular pH in intact hepatocytes by applying a flow cytometric technique to detect fluorescein-isothiocyanate-dextran radation is associated with a deficiency in the content of cathepsins B and L in lysosomes of ethanol-fed rats. 3 This (FITC-dextran) in acidic vesicles. Rats were pair-fed liquid diets containing either ethanol or iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 29 publications
(15 reference statements)
2
25
0
Order By: Relevance
“…Pulsechase analyses, using isolated hepatocytes demonstrated that the reduced lysosomal content of cathepsin L was the result of delayed trafficking of its nascent precursor and impaired processing to its mature catalytic form in cells from ethanol-fed rats [16,30,31] . Both flow cytometric and microscopy studies showed that vesicular movement and acidification of lysosomes in hepatocytes are both impeded after ethanol exposure [32,33] .…”
Section: Ethanol Consumption and The Hepatic Autophagic/lysosomal Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulsechase analyses, using isolated hepatocytes demonstrated that the reduced lysosomal content of cathepsin L was the result of delayed trafficking of its nascent precursor and impaired processing to its mature catalytic form in cells from ethanol-fed rats [16,30,31] . Both flow cytometric and microscopy studies showed that vesicular movement and acidification of lysosomes in hepatocytes are both impeded after ethanol exposure [32,33] .…”
Section: Ethanol Consumption and The Hepatic Autophagic/lysosomal Systemmentioning
confidence: 99%
“…glycogen) to nucleic acids. Macromolecular catabolism takes place inside the lysosomal lumen at hydrogen ion concentrations that are 500-fold higher (pH about 4.7) than that in the cytoplasm (pH about 7.4) [1] . Maintenance of such an acidic lysosomal interior occurs through the continuous action of ATP-dependent proton transporters that reside on its membrane.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Lysosomes are crucial for the breakdown of all forms of cellular macromolecules. They participate in the catabolic phase of macroautophagy (autophagy), which begins with the formation of double-membrane-bound autophagic vacuoles (AVs or autophagosomes) that envelop and sequester soluble Acute and chronic ethanol administration increase autophagic vacuole (i.e., autophagosome; AV) content in liver cells.…”
Section: Introductionmentioning
confidence: 99%
“…In mice fed with Lieber-DeCarli diet for 4 weeks, autophagy was elevated at a lower dose of ethanol, accounting for 29% of the caloric need, but was inhibited at a higher ethanol dose (accounting for 36% of the caloric need) (Lin et al 2013). Decrease in both the amount and the function of lysosomes was found in chronic alcohol treated rat livers, which may contribute to the autophagy suppression (Kharbanda et al 1996; Kharbanda et al 1997; Dolganiuc et al 2012). However, the liver injury is worse when autophagy is suppressed while enhancement of autophagy improves the condition (Lin et al 2013).…”
Section: Relevance Of Autophagy To Liver Diseasesmentioning
confidence: 99%